Rational use of imaging in acute pancreatitis and obstructive jaundice - Perea Guerrero, Humberto (2024)
The biliopancreatic pathology is one of most frequent causes of consultation in the gastroenterology specialty. In the present times this area of the human body is explored by diverse images (U.S., TAC, and RM). The use of them without a suitable direction can be from high cost and retardation diagnosis. In this article we took two clinical cases that they appeared in the Department of the Digestive Apparatus and with them we try to facilitate its use and indications. In the end we presented algorithms of diagnosis for the handling of this type of patients.